Fee‐for‐Service Medicare‐Enrolled Elderly Veterans Are Increasingly Voting with Their Feet to Use More VA and Less Medicare, 2003–2014. (27th August 2018) - Liu, Chuan‐Fen; Batten, Adam; Wong, Edwin S.; Fihn, Stephan D.; Hebert, Paul L.
Abstract : Objective: To examine the long‐term reliance on outpatient care at the population (i.e., system) level among fee‐for‐service Medicare‐enrolled elderly veterans in the Department of Veterans Affairs (VA) health care system and Medicare from 2003 to 2014. Data Sources/Study Setting: We analyzed a 5 percent random sample, stratified by facility, age, gender, and race, of Medicare‐enrolled veterans enrolled in a VA primary care panel using VA administrative data and Medicare claims. Study Design: We performed a repeated cross‐sectional analysis over 48 quarters. VA reliance was defined at the system level as the proportion of total visits (VA + Medicare) that occurred in VA. We examined four visit types and seven high‐volume medical subspecialties. We applied direct standardization adjusting for age, gender, and race using the 2010 population distribution of Medicare‐enrolled veterans. Principal Findings: Over the 12‐year period, VA provided the vast majority of mental health care. Conversely, veterans received slightly more than half of their primary care and most of their specialty care, surgical care, and seven high‐volume medical subspecialties through Medicare. However, reliance on VA outpatient care steadily increased over time for all categories of care. Conclusions: Despite the controversies about VA access to care, Medicare‐enrolled veterans, who have a choice of using VA or Medicare providers, appear to increase their use of VA care prior to the Choice Act.